Response to Sudduth’s “James Leininger Case Re-Examined” - Tucker, Jim (Journal of Scientific Exploration, 2022)
In the last issue, Michael Sudduth (2021) presented a reexamination of the case of James Leininger, who as a young boy appeared to remember the life of James Huston, a pilot killed during World War II. Sudduth clearly put a tremendous amount of time into exploring the case. Unfortunately, his report is filled with distortions, mischaracterizations, and at times, outright misinformation. There are too many instances to list every one, but large and small, they all contribute to an inaccurate picture that denigrates the credibility of James’s parents as informants and my competence as a researcher.